Consulting report – Canvia - Giribaldi del Risco, Romina Maria (Pontificia Universidad Católica del Perú, 2019)
Canvia is a Peruvian company owned by Advent International, which is one of the five largest private equity investment funds in the world. Canvia provides digital transformation services to clients to achieve the concrete business results, operating the following four business units: (a) service desk, (b) digital service, (c) business operation, and (d) cloud. The service desk unit is currently earning a low rate of margin. The main problem identified is a contract of service negotiated with Tiendas por Departamento Ripley, a Chilean retail company; and Banco Ripley Peru, a Chilean bank. According to the terms of this contract, Canvia provides their service desk services to both companies in Peru, by which the company receives a flat fee, independently of the number of tickets Canvia team resolves. This results in a constant revenue stream for Canvia and the increasing costs they have faced, resulted in financial losses to the company. However, at the moment, they are generating profits because of some changes introduced by the new Senior Manager. In this sense, the service desk unit, in particular Ripley’s account, is interested in look for any solution that generate a steady 20% profit margin. After reviewing the relevant literature, we have developed three alternatives of solutions, which are composed by several activities, which have been evaluated according to factors such as costs, innovation, risk, value added, feasibility and Canvia’s feedback. Our proposed solutions are a mix of these activities, which try to reduce costs but also increase Service Desk Unit’s flat revenues. The solutions are the implementation of a training website and the provision of training services to Ripley’s employees who manipulate embosadoras. However, since the success of these alternatives does not depend only on Canvia, it is concluded that the generation of a steady 20% profit margin for the Ripley account will not be possible if Canvia does not remain contracted by Ripley to provide additional services.

Canvia es una compañía peruana parte de Advent International, uno de los cinco fondos de inversión de capital privado más grandes del mundo. Canvia proporciona servicios de transformación digital a sus clientes para lograr resultados comerciales concretos, operando las siguientes cuatro unidades comerciales: (a) service desk, (b) servicio digital, (c) operación comercial y (d) cloud. La unidad de service desk está afrontando un bajo desempeño financiero. El principal problema identificado es el contrato de servicio negociado con Tiendas por Departamento Ripley, una empresa minorista chilena; y Banco Ripley Peru, un banco chileno. De acuerdo con los términos de este contrato, Canvia brinda sus servicios de service desk a ambas compañías, a cambio de una tarifa fija que no incrementa a pesar de que el número de tickets por resolver siga aumentando. Esto resulta en un flujo constante de ingresos para Canvia y un aumento significativo de costos, lo cual causó que la compañía llegue a tener pérdidas financieras. Sin embargo, actualmente están generando ganancias por algunos cambios realizados por el nuevo Gerente de Proyecto. En este sentido, la cuenta de Ripley en la unidad de service desk, está interesada en buscar cualquier solución que genere un margen estable del 20%. Después de revisar la literatura relevante, se han desarrollado tres alternativas de soluciones, compuestas por varias actividades, que han sido evaluadas de acuerdo a ciertos factores. La solución propuesta es una combinación de estas actividades - la implementación de un sitio web de capacitación y la provisión de servicios de capacitación sobre embosadoras - con el objetivo de reducir costos y también aumentar los ingresos fijos de la unidad. Sin embargo, dado que el éxito de estas alternativas no depende solo de Canvia, se concluye que la generación de un margen de beneficio estable del 20% para la cuenta de Ripley no será posible si Canvia no permanece contratado por Ripley para la provisión de servicios adicionales.
Keywords: Tecnología de la información; Transformación digital; https://purl.org/pe-repo/ocde/ford#5.02.04